Charlie cook's favourite book - Donaldson, Julia; Scheffler, Axel (London : Macmillan Children's Books, 2006)
Charlie Cook is reading a book about a pirate captain, who is reading a book about Goldilocks, who is reading about a knight, who is reading about a frog...From kings and queens to aliens and ghosts, there's something for everyone in Charlie's amazing book of adventure!
Keywords: Stories in rhyme